Detecting Genetic Associations between ATG5 and Lupus Nephritis by trans-eQTL - Yue-miao Zhang; Fa-juan Cheng; Xu-jie Zhou; Yuan-yuan Qi; Ping Hou; Ming-hui Zhao; Hong Zhang (Journal of Immunology Research)
Objectives. Numerous loci were identified to perturb gene expression in trans. As elevated ATG5 expression was observed in systemic lupus erythematosus (SLE), the study was conducted to analyze the genome-wide genetic regulatory mechanisms associated with ATG5 expression in a Chinese population with lupus nephritis (LN). Methods. The online expression quantitative trait loci database was searched for trans-expression single nucleotide polymorphisms (trans-eSNPs) of ATG5. Tagging trans-eSNPs were genotyped by a custom-made genotyping chip in 280 patients and 199 controls. For positive findings, clinical information and bioinformation analyses were performed. Results. Four trans-eSNPs were observed to be associated with susceptibility to LN (P < 0.05), including ANKRD50 rs17008504, AGA rs2271100, PAK7 rs6056923, and TET2 rs1391441, while seven other trans-eSNPs showed marginal significant associations (0.05 < P < 0.1). Correlations between the trans-eSNPs and ATG5 expression and different expression levels of ATG5 in SLE patients and controls were validated, and their regulatory effects were annotated. However, no significant associations were observed between different genotypes of trans-eSNPs and severity or outcome of the patients. Conclusion. Using the new systemic genetics approach, we identified 10 loci associated with susceptibility to LN potentially, which may be complementary to future pathway based genetic studies.